Pengaruh Pengeluaran Non-makanan terhadap Indeks Pembangunan Manusia Kabupaten Batang Hari Tahun 2015-2024 - Darma, Budi; Wulansari, Kasiyati Yunita; Rosmawati, Sri (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of non-food expenditure on the Human Development Index (HDI) in Batang Hari Regency during the period 2017–2024. The HDI is a comprehensive indicator that reflects the quality of human development through 3 (three) main dimensions, namely: health, education, and standard of living. This study uses a quantitative approach with secondary data sourced from the Central Statistics Agency (CSA). Data analysis was carried out using simple linear regression, supported by t-tests and coefficient of determination (R²). The results show that non-food expenditure has a positive and significant effect on the HDI. In addition, the adjusted R² value of 0.784 indicates that 78.4% of the variation in the HDI can be explained by changes in non-food expenditure. This finding suggests that increasing productive non-food expenditure can be an effective strategy to improve human development outcomes at the regional level.